Caracterização do groundnut ringspot virus (grsv) e seu vetor (Frankliniella schultzei) em melancia - Leão, Evelynne Urzêdo [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Watermelon (Citrullus lanatus) is considered one of the most important cucurbits in the world and Brazil is the fourth largest producer, with a total cultivated area of 90.000 ha and average production of about two million tons. In Brazil, viruses described in watermelon belong to the genus Potyvirus and Cucumovirus and Zucchini lethal chlorosis virus is the only species of Tospovirus genre described on this culture. Considering the high incidence of watermelon plants showing symptoms caused by virus during the 2012/2013 seasons and the presence of thrips in the field, the virus and the vector associated with the disease was identified and characterized. In the first chapter entitled Citrullus lanatus is a new natural host of Groundnut ringspot virus in Brazil, the species of tospovirus Groundnut ringspot virus(GRSV) was reported causing mosaic, deformation and necrotic lesions on leaves and fruits of watermelon. The GRSV was collected during the years 2012 and 2013 in producing areas of Presidente Prudente and Marília. GRSV from watermelon, differently from GRSV strains found on solanaceas, didn't infected tomato plants cv. Santa Clara and Mariana. Thrips specimens collected in the field were able to transmit GRSV to watermelon, peppers and Nicotiana species. This was the first report of natural infection of watermelon by GRSV. In the second chapter entitled A Taqman real-time RT - PCR assay for detection of Groundnut ringspot virus a quantitative PCR test was developed to efficiently detect GRSV from watermelon and from individual thrips. The test might be useful to detect GRSV and for further studies with this virus. The third chapter Efficient detection of Frankliniella schultzei (Thripidae: Thysanoptera) by real-time PCR reports the efficient detection of Frankliniella schultzei by the analysis of the mitochondrial gene cytochrome oxidase I (mtCOI). Thrips samples were ...

A melancia (Citrullus lanatus) é considerada uma das cucurbitáceas mais importantes no mundo e o Brasil é o quarto maior produtor, com área total cultivada de 90.000 ha e produção média de cerca de dois milhões de toneladas. No Brasil, há várias espécies de vírus descritas em melancia pertencentes ao gênero Potyvirus, Cucumovirus, sendo Zucchini lethal chlorosis virus a única espécie até então relatada no gênero Tospovirus. Considerando a alta incidência de plantas de melancia exibindo sintomas causados por vírus durante as safras 2012/2013 e a presença de tripes no campo, este trabalho teve como objetivo a identificação e caracterização do vírus e do vetor associado a sua transmissão. No primeiro capítulo intitulado Citrullus lanatus is a new natural host of Groundnut ringspot virus in Brazil, foi relatada a ocorrência de Groundnut ringspot virus (GRSV) em melancia ocasionando mosaico, deformações e lesões necróticas em folhas e manchas necróticas nos frutos. O GRSV foi coletado durante os anos de 2012 e 2013 nas regiões produtoras dos municípios de Presidente Prudente e Marília. O isolado de GRSV de melancia apresentou um círculo de hospedeiros semelhante aos isolados de GRSV provenientes de solanáceas, com a excessão de não infectar tomateiro cv. Santa Clara e Mariana. Espécimes de tripes coletados no campo foram capazes de transmitir o GRSV para melancia, pimentão e espécies de Nicotiana. Este foi o primeiro relato de infecção natural de melancia por GRSV. No segundo capítulo intitulado A Taqman real-time RT - PCR assay for detection of Groundnut ringspot virus foi possível detectar o GRSV por PCR quantitativo (qPCR) em amostras de melancia e em tripes individuais coletados no campo. A detecção do GRSV por qPCR poderá servir como uma ferramenta útil nos ...
Characterization of groundnut ringspot virus (grsv) and its vector (frankliniella schultzei) in watermelon
Keywords: Melancia - Doenças e pragas; Cucurbitacea - Resistencia a doenças e pragas - Aspectos geneticos; Reação em cadeia de polimerase; Watermelons Diseases and pests